THz cut-off frequency of multilayer armchair graphene nanoribbon tunnel field-effect transistors - Taufik Syah Mauludin; Maulana Ibrohim; Dadi Rusdiana; Lilik Hasanah; Siti Kudnie Sahari; Endi Suhendi (International Journal of Nanoelectronics and Materials (IJNeaM), 2025)
Graphene nanoribbons with tunable energy bandgaps present notable advantages for tunneling field-effect transistor (TFET) applications. These nanoribbons, composed of carbon atoms arranged in a hexagonal lattice resembling a honeycomb structure, feature a narrow width. The cut-off frequency of TFETs reflects their potential for developing low-energy, high-frequency devices. This study employed the Airy function approach to model the cut-off frequency of multilayer armchair graphene nanoribbon (AGNR) TFETs. Numerical calculations were conducted using computational programming in Wolfram Mathematica. The TFET’s potential profile was derived using the Airy function method to calculate transmittance, which was then used to determine the tunneling current through the Landauer equation and the Gauss-Legendre quadrature method. The tunneling current calculation enabled the estimation of the cut-off frequency. Results indicate that the cut-off frequency initially increases with gate voltage, reaches a peak, and subsequently decreases. Higher drain voltage and oxide thickness are associated with increased cut-off frequency, while longer channel lengths, wider multilayer graphene nanoribbons, and elevated temperatures tend to reduce it. Variations in AGNR layers significantly affect TFET performance, with trilayer AGNR TFETs achieving superior cut-off frequencies compared to their bilayer and monolayer counterparts.